2022-RA-466-ESGO Long-term responders (LTR) to rucaparib in recurrent ovarian cancer: a sub-group analysis from the rucaparib access (RAP) program in Spain by GEICO. (20th October 2022) - Yubero, Alfonso; Barquín, Aranzazu; Gaba, Lydia; Pajares, Bella; Reche, Piedad; Salvador, Carmen; Alarcón, Jesús; Manso, Luis; Marquez, Raúl; Fuentes, Jose; Madani, Julia; Costenla, Manuel; et al.
Abstract : Introduction/Background: Rucaparib is a PARPi approved as maintenance (MTN) for platinum (Pt)-sensitive recurrent HGOC, and as treatment (Tx) for BRCA -mutated recurrent HGOC patients. Real-world data about LTR patients from the RAP is analyzed here. Methodology: A retrospective GEICO study was performed at 22 hospitals that treated patients within the RAP. Women with HGOC received rucaparib (600 mg BID) in the MTN, Tx Pt-sensitive or Tx Pt-resistant setting. In this subanalysis, long-term response was defined as progression-free survival (PFS) ≥12 months for the MTN group and ≥6 months for the Tx group. Results: In the study 51 patients were recruited: 18 received rucaparib as MTN and 33 as Tx.In the MTN group, 6 patients (33.3%) were LTR. Of them, 2 patients (33.2%) harbored BRCA or RAD51C mutations. The median number of prior lines was 3 (2–6), being ≥5 in 33.2%, 66.6% had measurable disease and 50.0% achieved PR to prior Pt-based chemotherapy. In the Tx group, 10 patients (30.3%) were LTR. All of them harbored BRCA and/or RAD51C mutations. The median number of prior lines was 6 (2–9), with 60.0% receiving ≥5 prior lines, 60.0% were Pt-resistant and 60.0% had measurable disease. The median PFS of LTR was not achieved in the MTN group and was 10.9 months (95% CI: 7.0–16.7) in the Tx group. Adverse events (AE) of any grade were reported in 66.6% of LTR within the MTN group and in 100.0% within the Tx group, while AE of grade ≥3 occurred in 16.6% and 50.0%, respectively. No new safety signals were detected. At present, 3 and 1 patients are still receiving rucaparib as MTN and Tx, respectively. Conclusion: A durable response was achieved in a notable proportion of patients, despite their unfavorable conditions at treatment initiation. The safety profile of rucaparib in this real-world setting is consistent with that previously reported.